Nanotechnology and its Considerations in Poultry Field: An Overview - ABD EL-GHANY, W.A. (Journal of the Hellenic Veterinary Medical Society, 2019)
Nanotechnology is an emerging science field that in the years to come could have countless beneficial effects on every aspect of everyday life including animal farming. Recently, research in this sector has shown the potential for many different applications in Veterinary practice. In poultry farming in particular, various nanoparticles have been experimentally used for several purposes such as: alternative to antibiotics as growth promoters, as feed additives to enhance and improve the growth rate, performance, immunity, resistance to pathogens and increase the quality of meat. In laying hens, they can have a positive influence to both quantity and quality of eggs. Moreover, nanomaterials applied in embryonated chicken eggs can improve embryos development. The aim of this overview is to provide a description of potential nanotechnology applications for poultry sector and discuss any challenges or obstacles including the matters of safety of application of these nanomaterials in animals, in humans and of course in the environment.